Scientific basis of priority directions of the health care development for cardiac patients in city - L. I. Danilchenko (Zaporozhye State Medical University, 2017)
Objective: the scientific basis of priority directions of the health care development for cardiac patients in city according to public health system. Improving medical and demographic situation, increasing the availability and quality of care to all segments of the population is the priority task of modern health care system in Ukraine. Various aspects of population health due to diseases of the cardiovascular system and the issues of improving public health system and the system of cardiac care for the population, is the subject of many years researches. Cardiovascular diseases are leading causes of premature death, disability, temporary disability. According to the experience of developed countries in recent decades, the prevalence of this pathology and the severity of the harm to public health can reduce significantly in case of effective organization of medical-diagnostic process and prevention system. Specialized in patient care for patients suffering from cardiovascular diseases, is very expensive. At the same time, the number of patients with such pathology is high enough in ambulatory practice. Among them, special attention should be paid to those patients, who require daily monitoring, but do not require the round-the-clock stationary mode. The organization of inpatient forms of medical care for this category of patients is a very urgent task. Equally important are the training of personnel for the cardiology service, the sustainability of human resources, economic motivation, which ensures high quality, the effectiveness of complex labor processes.